The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.1677/joe.0.0470207
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Distribution of Radioactive Perchlorate in Rat and Guinea-Pig Thyroid Glands

Abstract: SUMMARY The thyroidal uptake of 36ClO4− and the effect of stable perchlorate ion and functional state of the thyroid, such as after long-term administration of propylthiouracil (PTU) or after hypophysectomy, on the uptake of 36ClO4− were studied in rats and guinea-pigs. Based on the analysis of uptake curves, radioactive inulin and sulphate spaces, and histological measurements of compartmental sizes of the thyroid, the relative concentrations of 36ClO4− in the various compartments were calculated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 0 publications
4
27
1
Order By: Relevance
“…This is in contradiction to previous studies showing that radiolabeled perchlorate was concentrated in thyroid tissue in vivo (9,10,32) and contrasts with the selectivity series based on physiological anion transport in thyroid tissue: , 34, 35). Recently, Dohan et al (14) published additional evidence of NIS-mediated active transport of perchlorate both in vivo and in vitro.…”
contrasting
confidence: 99%
“…This is in contradiction to previous studies showing that radiolabeled perchlorate was concentrated in thyroid tissue in vivo (9,10,32) and contrasts with the selectivity series based on physiological anion transport in thyroid tissue: , 34, 35). Recently, Dohan et al (14) published additional evidence of NIS-mediated active transport of perchlorate both in vivo and in vitro.…”
contrasting
confidence: 99%
“…Similar to the uptake data of Chow and Woodbury (1970), newly available data from our laboratory (Yu et al 2002) showed two distinct phases in the clearance of 36 ClO − 4 from the male rat thyroid after an IV dose. The first phase shows quick elimination, presumably diffusion from the follicle; the second phase is slower, suggesting slow release from a deep compartment (the lumen).…”
Section: Evidence For Perchlorate Transport From Thyrocytes Into the supporting
confidence: 69%
“…Indeed, ClO 4 Ϫ inhibition is one of the clearest hallmarks of NIS-mediated I Ϫ transport in both the thyroid and other tissues. Mechanistically, however, to date it has remained uncertain whether ClO 4 Ϫ is a NIS blocker or a transported substrate of NIS (2,(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%